Family structure and sex differences in postdisplacement outcomes - Daniel Rodriguez; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2001)
Labor force outcomes after an involuntary job loss tend to differ systematically between men and women, with women experiencing a lower probability of finding another job, a longer average duration of nonemployment, and larger losses in hours given reemployment. This study examines the role of family structure in such sex differences in postdisplacement outcomes. Data from the Panel Study of Income Dynamics indicate that unmarried women have postdisplacement outcomes similar to men whereas married women's outcomes differ considerably from those of men. The presence of children in the household appears to partially account for sex differences in postdisplacement outcomes, with women with young children less likely to be reemployed and more likely to not be in the labor force than their childless counterparts and than men.
Keywords: 330; Employment (Economic theory); Income distribution; Wages; Labor market